Estudo da flambagem local de perfis U enrijecidos em situação de incêndio - Alexandre Acipreste Rodrigues Costa (2012)
This work presents a study about the local buckling of cold formed lipped channel profiles in fire conditions. It was analyzed analytically and numerically the variation of the strength reduction factor of steel for the design of class 4 sections at elevated temperatures, k,, depending on the slenderness ratio of the cross section. The analytical models considered are based on the European and Brazilian standards. The numerical model is based on the finite element method. It was found that numerical results were different from the analytical results, which consider k, varying only with temperature. Theoretical values of the reduction factor were obtained and demonstrated a correlation with the slenderness ratio of the cross section.